Evaluación del proceso de semillas de amaranto mediante tecnología microondas. - Jiménez Jiménez, Germán Geovanny (2019)
Drying seeds in the province of Cotopaxi, in Ecuador, is carried out mainly to the air, taking advantage of solar energy. This drying method is widely used due to energy used for true process is free, and abundant in many parts of the world, especially in tropical countries. However, this procedure depend mainly on climatic conditions, which in Cotopaxi are not favourable, it causes a decrease in the viability and quality of the seeds, being exposed to their variations, being, also, susceptible to threat like environmental pollution. In addition, it involves a long drying time (more than 15 days), large spaces are required and non-uniform drying of the seeds. On the other hand, given fact agricultural activity and conservation of biodiversity a priority for Ecuadorian state, research into new technologies to improve drying process are a great interest. Therefore, the main objective of this research project is to evaluate amaranth drying process seed using microwave technology, this process was studied at 6 different temperatures (35, 40, 45, 50, 55, 60 °C). In the oven was placed a seed mass 100 g, until it is obtained final moisture of 12%. Per each temperature under study were conducted 5 experiments, measuring drying time, energy consumption and germination. Sequentially, drying process seed was evaluated in an electric oven, which was used to compare both drying technologies at the temperature 40 °C, in the same conditions as microwave technology, compared with the conventional technology, decreases drying time by 22%, decrease energy consumption by 75%. The germination tests were made automated germinating chamber at a temperature 25 °C and moisture 75%, showed that the temperature of 40 °C is the most suitable for the drying seed, since temperature which was obtained at a higher germination rate 86,8%. The result obtained in the job will contribute to the development of this drying technology, with consequent benefit for the improvement of the agricultural production of Cotopaxi province – Ecuador.